Kedudukan Sumber Hukum Islam Kedua (Hadis) Dalam Al-Qur'an - Muhammad Lathief Ilhamy Nasution (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2021)
Its position as a syara' argument means that in addition to the Qur'an, the sunnah of the Prophet also gives us instructions to know the eternal commandment of Allah which is called syar'i law. The word